HADIS-HADIS TENTANG PEREMPUAN SEBAGAI IMAM SHALAT - Suryadilaga, M. Alfatih (Musawa Jurnal Studi Gender dan Islam, 2011)
On the issue of women as imams, traditional Islamic discourses severely limits the chance of women to be leaders of a prayer, even in cases where the women are clearly the most competent, for reasons that are related to gender. A peculiar new view on such discourse is given; basing itself came from the hadith of Ibnu Waraqqah, it stands as a shahih hadith through an analysis of its sanad and matan. This new view expands the chances for women by allowing them to become imams. Though this view is currently considered deviant, its existence must be publicized as a branch of development of fiqh as a whole.